2011
DOI: 10.1007/s10495-011-0577-1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic microtubule network organization and maintenance depend on high cellular ATP levels and energized mitochondria

Abstract: Microtubule cytoskeleton is reformed during apoptosis, forming a cortical structure beneath plasma membrane, which plays an important role in preserving cell morphology and plasma membrane integrity. However, the maintenance of the apoptotic microtubule network (AMN) during apoptosis is not understood. In the present study, we examined apoptosis induced by camptothecin (CPT), a topoisomerase I inhibitor, in human H460 and porcine LLCPK-1α cells. We demonstrate that AMN was organized in apoptotic cells with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
1
19
0
4
Order By: Relevance
“…The amphiphilic nature of PFOS or PFOA suggests that their effects could primarily be associated with the membrane functions. To examine whether more cellular accessibility of PCP is attributed to the membrane effects induced by PFOS (or PFOA), the membrane properties of the cells were evaluated by exposing them to 100 lM PFOS (or PFOA) by FDA and LDH tests, which have been used for evaluating membrane permeability or integrity (Liu et al, 2008;Oropesa et al, 2011). The fluorescence intensity in FDA assay decreased about 18% (or 16%) when the cells were treated with PFOS (or PFOA) compared to the control (Fig.…”
Section: The Mechanism Of Enhanced Cytotoxicity Caused By Addition Ofmentioning
confidence: 99%
“…The amphiphilic nature of PFOS or PFOA suggests that their effects could primarily be associated with the membrane functions. To examine whether more cellular accessibility of PCP is attributed to the membrane effects induced by PFOS (or PFOA), the membrane properties of the cells were evaluated by exposing them to 100 lM PFOS (or PFOA) by FDA and LDH tests, which have been used for evaluating membrane permeability or integrity (Liu et al, 2008;Oropesa et al, 2011). The fluorescence intensity in FDA assay decreased about 18% (or 16%) when the cells were treated with PFOS (or PFOA) compared to the control (Fig.…”
Section: The Mechanism Of Enhanced Cytotoxicity Caused By Addition Ofmentioning
confidence: 99%
“…Thus, in vivo and in vitro experiments have shown that AMN was visualized predominantly in apoptotic cells with polarized/hyperpolarized mitochondria and, on the contrary, was dismantle in apoptotic cells with depolarized mitochondria. These observations suggest that AMN depends on energized mitochondria and high ATP levels [71]. Kinetics examination in pig LLCPK-1α cells expressing GFP-tubulin also showed that AMN was maintained during the execution phase of apoptosis until mitochondria depolarization marked the onset of secondary necrosis.…”
Section: Apoptotic Microtubules Organization and Maintenance Depend Omentioning
confidence: 75%
“…Therefore, it has been proposed that AMN formation depends on the bioenergetic status of apoptotic cells [71].…”
Section: Apoptotic Microtubules Organization and Maintenance Depend Omentioning
confidence: 99%
See 2 more Smart Citations